Metode Pembelajaran Bahasa Arab di Pondok Pesantren (Studi Kasus di Pondok Pesantren Sumatera Thawalib Parabek Bukittinggi) - Khairun Aini; Bela Ian Anisha (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract This research aims to identify the Arabic language learning methods used at Pondok Madrasah Sumatera Thawalib Parbek Bukittinggi. This research uses a qualitative approach with case study and monitoring methods. The results showed similarities with other madrasahs in terms of Arabic learning methods. Arabic is considered as an important learning module in Pondok Madrasah Sumatera Thawalib Parabek Bukittinggi. Arabic language learning in this pondok can be divided into two parts, namely (1) learning Arabic nahu (nahwu and sharaf), and (2) learning Arabic Muhaddtsah. Learning Arabic grammar (nahwu and sharaf) in Pondok Madrasah Sumatera Thawalib Parabek is intended for students who have completed their education at the MTS level, because at this stage the students are considered mature enough to read, write, and translate Arabic. In addition, in the muhaddatsah (conversation) learning system in Arabic at Pondok Madrasah Sumatera Thawalib Parabek Bukittinggi, there is one meeting a week, with an emphasis on the use of Arabic in daily conversation and special days of speaking Arabic. Each student is required to speak in Arabic on a predetermined day and place, and sanctions will be applied to students who violate these rules.AbstrakRiset ini bertujuan untuk mengidentifikasi metode pembelajaran bahasa Arab yang digunakan di Pondok Madrasah Sumatera Thawalib Parbek Bukittinggi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus dan pemantauan. Hasil penelitian menunjukkan kesamaan dengan pondok madrasah lainnya dalam hal metode pembelajaran bahasa Arab. Bahasa Arab dianggap sebagai modul pembelajaran yang penting di Pondok Madrasah Sumatera Thawalib Parabek Bukittinggi. Pembelajaran bahasa Arab di pondok ini dapat dibagi menjadi dua bagian, yaitu (1) pembelajaran nahu bahasa Arab (nahwu dan sharaf), dan (2) pembelajaran Muhaddtsah bahasa Arab. Pembelajaran gramatika bahasa Arab (nahwu dan sharaf) di Pondok Madrasah Sumatera Thawalib Parabek ini ditujukan untuk santri yang telah menyelesaikan pendidikan di tingkat MTS, karena pada tahap ini santri dianggap sudah cukup matang untuk membaca, menulis, dan menerjemahkan bahasa Arab. Selain itu, dalam sistem pembelajaran muhaddatsah (percakapan) dalam bahasa Arab di Pondok Madrasah Sumatera Thawalib Parabek Bukittinggi, terdapat satu kali pertemuan dalam seminggu, dengan penekanan pada penggunaan bahasa Arab dalam percakapan sehari-hari dan hari khusus berbicara Arab.